PENGELOLAAN SUPERVISI AKADEMIK DALAM PEMBELAJARAN DARING GURU MATA PELAJARAN IPS (STUDI KASUS DI SMP NEGERI 11 PADANG ULAK TANDING) - Yuniarti, Eni (Manajer Pendididikan, 2023)
This study aims to describe the management of academic supervision in online learning for social studies subjects at SMP Negeri 11 Padang Ulak Tanding. This research is a case study research. The research was conducted at SMP 11 Rejang Lebong. Research data obtained from interviews, observations and documentation. Research data analysis includes data reduction, data presentation, verification and conclusion drawing. The results showed that the management of academic supervision at SMP Negeri 11 Padang Ulak Tanding was in accordance with the applicable technical guidelines. The situational approach is used in the academic supervision of online learning. Principals need to do more maximum academic supervision to assist teachers in improving learning conditions during the Covid-19 pandemic.